STRATEGI PRODUKSI DAN PEMASARAN PT. SRIWIJAYA ALAM SEGAR DIPALEMBANG - Memi Martalia; Chandra Satria (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
Sriwijaya Alam Segar has a very close relationship with the world of marketing. This is one of the goals of the company that has received special attention, where the company feels it has a moral responsibility to participate in the problem of increasing people's appetite and buying interest. Thus, the company must be able to produce products in the form of quality food. This can be seen from its existence. the quality control department in charge of supervising the quality of the products that are sold and bought in the form of instant noodles, PT.Sriwijaya Alam Segar. PT.Sriwijaya Alam Segar still has irregularities, namely in the form of damaged and failed products. If the number of damaged products continues to increase, it can have an impact on increasing the cost of goods manufactured per unit of goods. This will have a negative impact on the level of competition in the business world.